PERANAN KEPALA DESA TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN - Andi Muhammad Amin; Mukhlis Hannan (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This study aims to determine the role of the Village Head Against Community Participation in the Development of South Aralle Village, MAMASA Regency. This is a descriptive study using a qualitative approach. Data collection techniques are done by observation, interview, and documentation. The research informants in this study were 1 Head of South Aralle Village as a key informant, Secretary of South Aralle Village and Chair of BPD South Aralle Village. Services as supporting informants. The data analysis technique used is an interactive model. Checking the validity of the data is done by triangulating sources and methods. From the results of the study showed that the Role of the Village Head Against Community Participation in the Development of South Aralle Village Mamasa Regency. seen from several aspects namely (Facilitator), (Mediator), and (Motivator).